"Speech development tools for preschool children" (Journal of Pedagogical Inventions and Practices, 2022)
In our Republic, which is boldly pursuing the path of independent development and striving to build a democratic society based on the rule of law, a society is being built to ensure the free and prosperous life of everyone, all opportunities are being created for young people to be educated. In particular, the implementation of the National Training Program clearly shows that the mother tongue is the main subject of study at all stages of the education system, and in order to master the subjects, first of all, it is necessary to think correctly, expressively, systematically and creatively. Because our future, as the First President of the Republic of Uzbekistan A. Karimov said: "It requires innovative, modern professionals." This article is written about speech development in preschool children, and means of speech enhancement.